Brentuximab Vedotin Combined With Chemotherapy in Patients With Newly Diagnosed Early-Stage, Unfavorable-Risk Hodgkin Lymphoma. Issue 20 (10th July 2021) - Kumar, Anita; Casulo, Carla; Advani, Ranjana H.; Budde, Elizabeth; Barr, Paul M.; Batlevi, Connie L.; Caron, Philip; Constine, Louis S.; Dandapani, Savita V.; Drill, Esther; Drullinsky, Pamela; Friedberg, Jonathan W.; et al.
Abstract : PURPOSE: To improve curability and limit long-term adverse effects for newly diagnosed early-stage (ES), unfavorable-risk Hodgkin lymphoma. METHODS: In this multicenter study with four sequential cohorts, patients received four cycles of brentuximab vedotin (BV) and doxorubicin, vinblastine, and dacarbazine (AVD). If positron emission tomography (PET)-4–negative, patients received 30-Gy involved-site radiotherapy in cohort 1, 20-Gy involved-site radiotherapy in cohort 2, 30-Gy consolidation-volume radiotherapy in cohort 3, and no radiotherapy in cohort 4. Eligible patients had ES, unfavorable-risk disease. Bulk disease defined by Memorial Sloan Kettering criteria (> 7 cm in maximal transverse or coronal diameter on computed tomography) was not required for cohorts 1 and 2 but was for cohorts 3 and 4. The primary end point was to evaluate safety for cohort 1 and to evaluate complete response rate by PET for cohorts 2-4. RESULTS: Of the 117 patients enrolled, 116 completed chemotherapy, with the median age of 32 years: 50% men, 98% stage II, 86% Memorial Sloan Kettering–defined disease bulk, 27% traditional bulk (> 10 cm), 52% elevated erythrocyte sedimentation rate, 21% extranodal involvement, and 56% > 2 involved lymph node sites. The complete response rate in cohorts 1-4 was 93%, 100%, 93%, and 97%, respectively. With median follow-up of 3.8 years (5.9, 4.5, 2.5, and 2.2 years for cohorts 1-4), the overall 2-year progression-free and overall survival were 94% and 99%, respectively. In cohorts 1-4, the 2-year progression-free survival was 93%, 97%, 90%, and 97%, respectively. Adverse events included neutropenia (44%), febrile neutropenia (8%), and peripheral neuropathy (54%), which was largely reversible. CONCLUSION: BV + AVD × four cycles is a highly active and well-tolerated treatment program for ES, unfavorable-risk Hodgkin lymphoma, including bulky disease. The efficacy of BV + AVD supports the safe reduction or elimination of consolidative radiation among PET-4–negative patients.